Retraction: Development of functional hydrogels for heart failure. Issue 15 (12th April 2021) - Han, Yanxin; Yang, Wengbo
Abstract : Retraction for 'Development of functional hydrogels for heart failure' by Yanxin Han et al., J. Mater. Chem. B, 2019, 7, 1563–1580, DOI: ; 10.1039/C8TB02591F .